2021
DOI: 10.1186/s13098-021-00654-3
|View full text |Cite
|
Sign up to set email alerts
|

A review of flash glucose monitoring in type 2 diabetes

Abstract: Background Continuous glucose monitoring systems are increasingly being adopted as an alternative to self-monitoring of blood glucose (SMBG) by persons with diabetes mellitus receiving insulin therapy. Main body The FreeStyle Libre flash glucose monitoring system (Abbott Diabetes Care, Witney, United Kingdom) consists of a factory-calibrated sensor worn on the back of the arm which measures glucose levels in the interstitial fluid every minute and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 26 publications
1
13
0
2
Order By: Relevance
“…The decreasing number of hypoglycemic events supports this over time (9.54 ± 1.73 3 -6 months before using the flash glucose monitoring system to 0.52 ± 0.50 last six months of the study). These results are consistent with current literature suggesting that the flash glucose monitoring system decreases the incidence of hypoglycemic events [20] [21] [22] [23] [24].…”
Section: Discussionsupporting
confidence: 93%
“…The decreasing number of hypoglycemic events supports this over time (9.54 ± 1.73 3 -6 months before using the flash glucose monitoring system to 0.52 ± 0.50 last six months of the study). These results are consistent with current literature suggesting that the flash glucose monitoring system decreases the incidence of hypoglycemic events [20] [21] [22] [23] [24].…”
Section: Discussionsupporting
confidence: 93%
“…The essence of this result is that on the basis of clinicians' adjustment of diabetic therapy according to retrospective FGM data once a month, patients can improve their blood glucose better, modulating their diet and exercise according to visible FGM data more effectively compared with regular SMBG. By using the retrospective FGM as a control, the present study was able to compare TIR between the two groups and partially eliminated the interference of physician-led drug adjustment, both of which have not been discussed in previous studies comparing FGM with SMBG (17)(18)(19).…”
Section: Discussionmentioning
confidence: 97%
“…Two large randomized controlled trials have demonstrated a signi cant reduction of hypoglycaemic events and GV, as well as increase in TIR and patients' satisfaction in subjects with T1DM (30) and insulin treated T2DM (31) managed with FGM, as compared to SMBG. In addition, real-world studies showed greater reductions in HbA1c levels using FGM compared to SMBG (32,33), also showing that the number of glucose scans is inversely associated with time spent in hypoglycaemia or hyperglycaemia and is positively correlated with TIR (34). Consequently, besides hypoglycaemic, and hyperglycaemic episodes, according to the panel, also GV and TIR should now be assessed as part of the routine management of diabetes (10).…”
Section: Discussionmentioning
confidence: 99%